Harmonila: Revitalisasi Budidaya Ikan Nila berbasis RAS-IOT dan PLTS guna Meningkatkan Produktivitas dan Perekonomian Desa Borong Pa’la’la, Kabupaten Gowa - Fitriyanti Mayasari; Muh. Krishna Moorthy Saud; Ahmad Yusuf Suandi; Ahmad Ridha (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
The fish farming system in Indonesia has been widely developed because of its great potential. A common problem in fish farming systems is a decrease in water quality, therefore water replacement must be carried out continuously. Apart from that, the water is also susceptible to contamination and causes suboptimal fish growth. This problem is also experienced by fish farmers in Borong Pa'la'la Village, Pattalassang District, Gowa Regency, who produce stunted Tilapia fish, thus Tilapia cultivation activities are not very popular with residents. Community service activities (PkM) from the Department of Electrical Engineering, Faculty of Engineering, Hasanuddin University, provide solutions for revitalizing Tilapia fish cultivation by utilizing the Recirculator Aquaculture System (RAS) which is integrated with the Internet of Things (IoT) and Solar Power Plants (PLTS). The aim of this activity is to increase the production of Tilapia fish cultivation both in terms of quantity produced and in terms of the quality of the fish produced. Apart from that, it is hoped that there will be an increase in the knowledge and interest of the youth in effective and sustainable Tilapia cultivation activities as well as the integration of technology into these cultivation activities. PkM activities are carried out in the form of socialization and training for residents, as well as building a RAS-IoT-PLTS system for Tilapia cultivation. Based on the results of quantitative analysis of pre-test (before training) and post-test (after training) measurements by training participants, an increase in the level of understanding of participants reached 77 – 85%, which was quite understanding to very understanding of the RAS-IoT-PLTS system as a whole, compared to conditions before training was carried out. This indicates that this activity has achieved the expected target.